The Concept of Usury (Ribā) according to MTR - Sri Wigati (Maliyah : Jurnal Hukum Bisnis Islam, 2021)
Of the many anti-usury movements in Indonesia, one of them is a community called the Society Without Usury (Masyarakat Tanpa Ribā hereinafter referred to as MTR). This community already has networks in several regions in Indonesia, which carry out the mission of da'wah to spread the understanding of usury and help people who are caught in problems with usury. The existence of this community aims to become a place of consultation as well as complaints for victims of usury. This research was conducted to answer the questions; What is the history of the emergence of MTR which echoes the spirit of living without usury? The type of this research is a qualitative research and uses field research. The approach that used in this research is phenomenology approach which sees changes in people's ways of thinking in life. Data collection techniques in this research are participatory observations, interviews and documentations. The results of this research show that: the history of the emergence of MTR is due to awareness as an anti-usury da'wah community, social movement, self-liberation from debt.